Narasi Futuristik Lingkungan dalam Novel Cerita Bumi Tahun 2683 Karya Aesna - Dwiky Yoga Karuniawan; Suyatno Suyatno; Yuniseffendri Yuniseffendri (STKIP Singkawang, 2025)
This study examines the structure of futuristic environmental narratives as represented in the novel Cerita Bumi Tahun 2683 by Aesna. The purpose of this research is to describe the role of the narrator, the focalization or point of view, and the sequence of the fabula contained in the novel, based on Mieke Bal’s narratology theory. This study employs a descriptive qualitative approach within the framework of narratology. The data source in this research is a science fiction novel that explicitly addresses futuristic environmental issues, namely Cerita Bumi Tahun 2683 by Aesna. The research data consist of narrative excerpts that represent futuristic environmental narration. Data collection was conducted using the reading and note-taking technique to obtain data relevant to the research topic. Data analysis employed content analysis based on Mieke Bal’s narratology theory. The findings reveal that the narrator plays roles such as enlivening the story, deepening the content, and influencing the interpretation of the narrative. Furthermore, three types of focalization were identified: zero focalization, internal focalization, and external focalization. In addition, the sequence of the fabula was found to be constructed through events, time, and setting.